Azole Antifungal Consumption in Community Pharmacy Sales in Mainland Portugal: Trend Analysis from 2014 to 2023 - Sofia Moura; Paulo Duarte; Ana Sofia Oliveira; José Martinez-de-Oliveira; Ana Palmeira-de-Oliveira; Joana Rolo (Antibiotics)
Background/Objectives: Excessive or inadequate use of antimicrobial drugs may lead to the emergence of resistant strains. For this reason, it is important to monitor consumption indicators to assess drugs’ utilization over time. This study aimed to analyze the consumption of medically prescribed azole antifungal drugs in mainland Portugal from 2014 to 2023, focusing on those directed to genital infections: fluconazole, isoconazole, itraconazole, and sertaconazole. Methods: For each drug, the evaluated parameters were the total number of packages, number of packages per 1000 inhabitants, defined daily dose (DDD) per 1000 inhabitants per day, and total costs. For this purpose, we used data from community pharmacies’ sales, which are available through INFARMED (the Portuguese national authority on medicines and health products). Results: Several trends emerged from data analysis. The COVID-19 pandemic negatively affected the consumption of all azole antifungal drugs included in this study. However, after 2020, fluconazole and sertaconazole consumption has been increasing. In the specific case of fluconazole, there was an increase in expenditure, although the total number of packages suffered a decrease over the 10-year study period. Additionally, the defined daily dose (DDD) per 1000 inhabitants per day for fluconazole and itraconazole was lower compared to estimates from the last available survey (2009). Conclusions: Although our findings represent a lesser pressure on fungi, further monitoring is needed to better understand the evolution of fluconazole and itraconazole consumption over time, particularly due to the trends observed in this study.